(untitled) (Journal of the College of Basic Education, 2026)
Text sociology seeks to explore the act of reading in a fundamental and profound way. A text is not complete and cannot realize its true essence until it is read. Sociological criticism is one of the new and influential methods for analyzing literary texts, particularly the novel. Based on this, the researcher in this research attempts, through the descriptive-analytical approach, to read the text of the novel "Adeni Incense" by Ali Al-Maqri, and to reach the social and ideological issues in which the Yemeni society lived and which the novel tried to portray. The aim of choosing this novel is its importance in portraying the Yemeni society and reaching the Arab city that celebrates multiculturalism. With manifestations of freedom, art, beauty, tolerance, and encounter with others within a context that depicts the ideological circles in Aden society. The results indicate that this novel expresses a specific ideology, which can be expressed through the unification of all the components of the novel’s structure. There is a strong relationship between the elements of time, place, social classes, fictional characters, and the social problems presented in the novel